PROBLEMATIKA GENDER DALAM ISLAM (Telaah Pendekatan Kontekstual) - Mubarok, Ahmad Sahal; Saekhoni, Saekhoni; Fatoni, Ahmad Sirfi (Institut Agama Islam Imam Ghozali, 2020)
This article examines about gender problem by using a contextual approach. This approach means understanding Islam in accordance with the current situation, in this corridor of course the situation will always change, the situation past, present and future will definitely experience differences. Need to know carefully, until now gender issues still has a serious impact on the global arena. Why is that, because this issue is often clashed with religion dogmas, especially Islam religion which is the tendency to not generalize in its laws has subordinate the woman’s party. It appears in the matter of legacy and testimony distribution. This type of research is a qualitative research which has a descriptive analysis characteristic. As for the research results among others: 1) By using the contextual approach, talking about the relationship between men and women in islam in principle can be considered the same as talking around the parallel between the both of them. Because in the religion of Islam in principle the relationship between the both of sexes is equal before Allah as is evident in the surah Al-Hujura@t verse 13. In addition, the great mission of Islam is rahmatan li al-alamin; 2) The government policies including in the world of work, should pay serious attention to equal opportunities for both men and women in the supply of available employment opportunities regardless of gender construction, so that it will produce a justice without inequality. For example, a green revolution program designed without considering gender aspects, in which to harvest the rice is used by a sickle cutting system, not by ani-ani, even though that tool is attached to the women; 3) The Koran as a reference to the principle of society recognizes that the position of men and women is equal. The both of them are created from one nafs, which is the one has no advantage over the other. Even the Koran doesn’t explicitly explain that Hawa was created from Adam’s rib so that her status was lower. On that basis, the principle of the Koran for men and women is the same, where the right of the wife is recognized as equal to the right of the husband, including inheritance and testimony. The action that must be needed now is to bulid a proportional synthesis between the Koran, classical Islamic literature and modern science in order to reinterpret gender issue in depth which is the majority of his understanding is marginalize the women.